Effect of Physical Fitness, and Self-Concept on the Performance of Teachers of Physical Education in Ambon City - Siti Divinubun (Future Science, 2021)
Introduction: This study aim at determining the effect of Physical fitness, self-concept and sports motivation on performance of teacher elementary school. Method: The research used quantitative approach with survey method and path analysis applied in testing hypothesis. The research was conducted at Ambon City with a sample of 50 teachers physical education elementary school selected through random sampling. Data analysis technique is an analysis regression (ANAVA) with F test and t-test at a significance level of α = 0.05, and path analysis. Results: The results of this study indicate that: (1) there is positive direct effect of physical fitness on performance of teachers in the amount of 0.326, (2) there is positive direct effect of self-concept on performance of teachers in the amount of 0.333, (3) there is positive direct effect of self-concept on performance of teachers in the amount of 0.355, (4) there is positive direct effect of physical fitness on self-concept in the amount of 0.318, (5) there is positive direct effect of on self-concept in the amount of 0.307. Conclusion: The conclusion showed that physical fitness, self-concept and sports motivation are important determinants to decrease the performance of teachers on physical education at elementary school of Ambon City.